Biological Effects of Activated Carbon on Benthic Macroinvertebrates are Determined by Particle Size and Ingestibility of Activated Carbon. (8th November 2021) - Rämö, Robert A.; Honkanen, Johanna; Nybom, Inna; Gunnarsson, Jonas S.
Abstract: The application of activated carbon (AC) to the surface of contaminated sediments is a promising technology for sediment remediation in situ. Amendment with AC has proved to be effective in reducing bioavailability and sediment‐to‐water release of hydrophobic organic contaminants. However, AC may cause positive or negative biological responses in benthic organisms. The causes of these effects, which include changes in growth, reproduction, and mortality, are unclear but are thought to be related to the size of AC particles. The present study investigated biological response to AC ranging from ingestible powdered AC to noningestible granular AC in two benthic deposit feeders: the polychaete Marenzelleria spp. and the clam Limecola balthica (syn. Macoma balthica ). In the polychaete, exposure to powdered AC (ingestible) reduced both dry weight and carbon assimilation, whereas exposure to granular AC (noningestible) increased both dry weight and carbon assimilation. Responses in the clam were similar but less pronounced, indicating that response levels are species‐specific and may vary within a benthic community. In addition, worms exposed to the finest ingestible AC particles had reduced gut microvilli length and reduced gut lumen, indicating starvation. These results strongly suggest that biological responses to AC depend on particle ingestibility, whereby exposure to ingestible particles may cause starvation through reduced bioavailability of food coingested with AC or due to rejection of AC‐treated sediment as a food source. Environ Toxicol Chem 2021;40:3465–3477. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.